KONTRIBUSI GURU DALAM UPAYA PENGUATAN KARAKTER BERBASIS AJARAN TRI KAYA PARISUDHA PADA SEKOLAH RAMAH ANAK DI SD NO. 3 SEMPIDI - Ryan Widya Samudra; Ni Komang Sutriyanti; Ida Ayu Gde Wulandari (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
This study aims to analyze the contribution of teachers, identify the obstacles faced, and dissect the impact of the teacher's contribution in strengthening character based on Tri Kaya Parisudha teachings in Child-Friendly Schools at SD No. 3 Sempidi. Character issues such as bullying in elementary schools underlie the urgency of integrating Hindu moral values that align pure thoughts (Manacika), words (Wacika), and deeds (Kayika). This research employed a qualitative descriptive approach. Primary data were gathered through observations and in-depth interviews with the principal, Hindu religion teacher, special assistant teacher, and students, while secondary data were obtained via documentation study. The collected data were analyzed interactively through the stages of data reduction, data display, and conclusion drawing. The results show that teachers contribute significantly as moral role models through integrated positive discipline practices. The obstacles faced include internal factors such as diverse hereditary traits, emotional instability, and varied learning interests, alongside external factors stemming from influences in the family, school, and community environments. This contribution yields positive transformative impacts on enhancing students' religiosity, inclusive tolerance among religious groups, and improving students' social etiquette and politeness in daily life. This study confirms the effectiveness of synergizing local religious wisdom with child-friendly school programs to realize a safe learning space free from violence.